Clinical relevance of multiple antibody specificity testing in anti-phospholipid syndrome and recurrent pregnancy loss - Tebo, A E (Blackwell Science Inc, 2008)
We wanted to evaluate whether testing for anti-phosholipid antibodies other than anti-cardiolipin (aCL) and anti-beta-2 glycoprotein I (aβ(2)GPI) immunoglobulin (Ig)G and IgM identifies patients with recurrent pregnancy loss (RPL) who may be positive for anti-phospholipid syndrome (APS). In a cross-sectional study comprising 62 patients with APS, 66 women with RPL, 50 healthy blood donors and 24 women with a history of successful pregnancies, we tested IgM and IgG antibodies to phosphatidic acid, phosphatidyl choline, phosphatidyl ethanolamine, phosphatidyl glycerol, phosphatidyl inositol and phosphatidyl serine with and without beta-2 glycoprotein I (β(2)GPI) from a single manufacturer as well as aCL and aβ(2)GPI antibodies. Diagnostic accuracies of individual and combined anti-phospholipid (aPL) assays were assessed by computing sensitivities, specificities, positive predictive values and negative predictive values together with their 95% confidence intervals. There was a general trend for increased sensitivities in the presence of β(2)GPI co-factor with significant effect for certain specificities. The overall combined sensitivity of the non-recommended aPL assays was not significantly higher than that of the aCL and aB2GPI tests. Multiple aPL specificities in RPL group is not significantly different from controls and therefore of no clinical significance.